2010
DOI: 10.4196/kjpp.2010.14.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Are Spinal GABAergic Elements Related to the Manifestation of Neuropathic Pain in Rat?

Abstract: Impairment in spinal inhibition caused by quantitative alteration of GABAergic elements following peripheral nerve injury has been postulated to mediate neuropathic pain. In the present study, we tested whether neuropathic pain could be induced or reversed by pharmacologically modulating spinal GABAergic activity, and whether quantitative alteration of spinal GABAergic elements after peripheral nerve injury was related to the impairment of GABAergic inhibition or neuropathic pain. To these aims, we first analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…In the literature, there are somewhat conflicting data on the relationship between changes in spinal GABAergic functions, GAD expression, and signs of neuropathy. It has recently been demonstrated that there was no relationship between the presence or absence of hypersensitivity and quantitative changes in spinal “GABAergic elements,” including GAD 65 and GAD 67, in spite of attenuating effects by intrathecal administration of GABA agonists . These findings are in accordance with some other studies that have failed to present evidence for an increased GABAergic cell apoptosis, changes in GABA bouton density, and in vesicular GABA transporters after nerve injury .…”
Section: Discussionsupporting
confidence: 83%
“…In the literature, there are somewhat conflicting data on the relationship between changes in spinal GABAergic functions, GAD expression, and signs of neuropathy. It has recently been demonstrated that there was no relationship between the presence or absence of hypersensitivity and quantitative changes in spinal “GABAergic elements,” including GAD 65 and GAD 67, in spite of attenuating effects by intrathecal administration of GABA agonists . These findings are in accordance with some other studies that have failed to present evidence for an increased GABAergic cell apoptosis, changes in GABA bouton density, and in vesicular GABA transporters after nerve injury .…”
Section: Discussionsupporting
confidence: 83%
“…such that GABAergic inputs can become excitatory (De Koninck, 2007), enhancing GABAergic neurotransmission at spinal level has regularly been found to exert antinociceptive effects in neuropathic pain models (Braz et al, 2012;Lee et al, 2010), notably through activation of specific GABA A R containing the a2 and/or a3 subunits (Knabl et al, 2008;Munro et al, 2009). Direct electrophysiological recordings of dorsal horn neurons coupled to pharmacological and/or gene knock-in interventions specifically at a2 and/or a3 subunits-containing GABA A R would be of special interest to assess whether GABA A R-mediated anti-hyperalgesic effects of 5-HT 7 R activation involve these receptor subtypes.…”
Section: Discussionmentioning
confidence: 96%
“…These observations indicated that the standardized MC has potential to interact with the GABA A & GABA B receptors and support the involvement of GABAergic system. Reduction in the levels of GABA and GABA receptors is well documented in different animal models of neuropathic pain (Eaton et al, 1998) and GABA agonists such as muscimol and baclofen showed beneficial effects on neuropathic pain (Lee et al, 2010).…”
Section: Possible Mechanisms Of Action Of Standardized MC In Vincristmentioning
confidence: 99%